2012
DOI: 10.1002/hed.22009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sebaceous carcinoma of the head and neck: Implications for lymph node management

Abstract: The incidence of nodal disease was higher with eyelid tumors. Sentinel lymph node biopsy can be considered for eyelid tumors, but not for non-eyelid head and neck tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 11 publications
3
74
2
4
Order By: Relevance
“…Extra-ocular facial SC is a rather uncommon phenomenon. It is suggested that extra ocular SC has a better prognosis than ocular SC [3,10,15]. Local cutaneous or subcutaneous metastases like in this case report are very uncommon.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Extra-ocular facial SC is a rather uncommon phenomenon. It is suggested that extra ocular SC has a better prognosis than ocular SC [3,10,15]. Local cutaneous or subcutaneous metastases like in this case report are very uncommon.…”
Section: Discussionmentioning
confidence: 61%
“…Early lymphogenous and haematogenous metastases are documented in up to 25 % of cases [2,3]. This probability has shown to be less in extra-ocular sites [10]. Accordingly, extra-ocular multifocal facial metastasizing SC is nearly unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 It is commonly found on the head and neck and has a propensity to occur on the eyelid in association with the meibomian glands. In a recent review of the surveillance, epidemiology and end results (SEER) database, Tryggvason et al evaluated 1836 cases and identified a male predominance (85%) occurring at an average age of 70.…”
Section: Sebaceous Carcinomamentioning
confidence: 99%
“…Extraorbital sebaceous carcinoma is less aggressive when compared with periorbital because of a reduced tendency for regional metastasis (1.4% for extraorbital vs. 4.4% for periorbital). 2 The parotid gland forms frequent site of origin because of presence of pluripotential cells or ectopic sebaceous glands. Metastasis to parotid gland has also been reported.…”
Section: Introductionmentioning
confidence: 99%